2005
DOI: 10.1172/jci23853
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SOCS7 leads to enhanced insulin action and enlarged islets of Langerhans

Abstract: NIDDM is characterized by progressive insulin resistance and the failure of insulin-producing pancreatic β cells to compensate for this resistance. Hyperinsulinemia, inflammation, and prolonged activation of the insulin receptor (INSR) have been shown to induce insulin resistance by decreasing INSR substrate (IRS) protein levels. Here we describe a role for SOCS7 in regulating insulin signaling. Socs7-deficient mice exhibited lower glucose levels and prolonged hypoglycemia during an insulin tolerance test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 54 publications
0
84
0
Order By: Relevance
“…19 However, reported evidence in HCV infection is controversial: while some works attested that HCV 1b induces an increase of SOCS-1/SOCS-3 expression both in vivo and in vitro, 12,[42][43][44] others documented a decreased SOCS-1 level. 45 In our model, SOCS-1 and SOCS-3 levels are unchanged irrespectively of the genotype, while the level of SOCS-7, recently shown to be involved in IRS-1 degradation, 20 is increased in genotype 3a only. We have no explanation for the observed discrepancy with the published results concerning 1b.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…19 However, reported evidence in HCV infection is controversial: while some works attested that HCV 1b induces an increase of SOCS-1/SOCS-3 expression both in vivo and in vitro, 12,[42][43][44] others documented a decreased SOCS-1 level. 45 In our model, SOCS-1 and SOCS-3 levels are unchanged irrespectively of the genotype, while the level of SOCS-7, recently shown to be involved in IRS-1 degradation, 20 is increased in genotype 3a only. We have no explanation for the observed discrepancy with the published results concerning 1b.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, as many studies have proposed a molecular mechanism of insulin resistance due to increased proteasomal degradation of IRS-1 through SOCS-1 and 3, 12,19,28-30 we measured the expression levels of these 2 members of the SOCS family in our in vitro model, together with that of SOCS-7, recently reported to modulate insulin signaling. 20 SOCS-1 and SOCS-3 mRNA levels were unchanged following transfection with both core proteins (data not shown). However, SOCS-7 mRNA levels were significantly higher in cells expressing the core protein 3a (but not in those transfected with core protein 1b) (Fig.…”
Section: Role Of Hcv Core 1b and 3a On Irs-1 Proteasomal Degradation mentioning
confidence: 87%
See 1 more Smart Citation
“…Another study suggests that SOCS6 interacts with IRS4 in response to insulin [42] and SOCS7, a close homolog of SOCS6, also associates with both INSR and IRS1 [43]. It has also been shown that overexpression of SOCS6 leads to inhibition of tyrosine phosphorylation of IRS1 indicating that SOCS6 not only regulates substrate turnover, but it also competes with the substrate for association to the INSR [40].…”
Section: Socs6 Is a Regulator Of Insulin Receptor Signalingmentioning
confidence: 99%
“…The observation of gigantism in SOCS2-deficient mice provides clear evidence that SOCS2 is a negative regulator of GH signaling (29). Moreover, there is a growing body of evidence suggesting a role for SOCS proteins in insulin signaling (4,17,24,42).…”
mentioning
confidence: 99%